Analisis Spasial Rute Pengangkut Sampah Terhadap ISPU PM10 dan Efisiensi Waktu Tempuh - Cangara, Iin Fitrianty Suaib; Nur, Achmad Irfan; Maghfirah, Alifah Dhiya; Suwahyo, Chaidir (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
This study aims to analyze the performance of solid waste transportation routes to the Bantargebang Integrated Waste Treatment Facility (TPST Bantargebang) in Bekasi City by focusing on two main indicators, namely travel time efficiency and environmental impact measured by the Air Pollution Standard Index (PM10). The research method integrates Geographic Information System (GIS)-based modeling, route simulation, and comparative analysis between the existing route and three alternative routes (Route A, Route B, and Route C). Travel data were examined to identify traffic load patterns, travel duration, and the potential reduction of PM10 concentrations along each corridor. The results indicate that the existing route demonstrates superior travel time efficiency but is associated with the highest PM10 levels. Routes A and C show improvements in air quality through reduced PM10 concentrations; however, these improvements are accompanied by significantly longer travel times. Among all alternatives, Route B is identified as the most optimal option, as it achieves a substantial reduction in PM10 levels while maintaining travel time efficiency comparable to the existing route. These findings highlight the trade-off between operational efficiency and environmental sustainability and demonstrate that spatial-based route optimization can serve as an effective strategy to enhance the performance of urban waste transportation systems while mitigating air pollution impacts.